Sodium-glucose cotransporter 2 inhibitors—but not insulin—enhance renal branched-chain amino acid catabolism - Sakamoto, Moeko; Hasuzawa, Nao; Wang, Lixiang; Tashiro, Kyoko; Kitamura, Miyuki; Iwata, Shimpei; Wada, Nobuhiko; Nomura, Seiji; Moriyama, Sawako; Gobaru, Mizuki; Inoguchi, Yukihiro; Nagayama, Ayako; et al. (Frontiers in Endocrinology, 2025)
Aims/hypothesisSodium–glucose cotransporter 2 inhibitors (SGLT2i) confer cardio-renal protection, and recent work implicates enhanced branched-chain amino acid (BCAA) catabolism as a potential mechanism in the heart. Whether SGLT2i also promotes renal BCAA catabolism is largely unknown. We hypothesized that SGLT2i enhances renal BCAA catabolism independently of glycemic effects.MethodsWe conducted a prospective, single-center, open-label, nonrandomized, controlled clinical study in patients with type 2 diabetes stably treated with insulin, who were assigned to dapagliflozin (5 mg/day with dose-reduced insulin; n=8/9 completed) or insulin dose-up (n=5/8 completed). At 12 weeks, changes in urinary and plasma metabolites and short-chain acylcarnitines related to BCAA catabolism were quantified. To explore mechanisms, 10-week-old db/db mice received luseogliflozin (10 mg/kg/day, p.o.) or insulin glargine (10 U/day, s.c.) for 4 weeks; renal histology, mRNA and protein expression of key enzymes involved in BCAA catabolism, including branched-chain aminotransferase 2 (BCAT2), branched-chain ketoacid dehydrogenase (BCKDH), and BCKD kinase (BCKDK), were assessed.ResultsDapagliflozin treatment induced greater increases in urinary excretion of three BCAA-derived metabolites—3-hydroxypropionic acid, C5-OH carnitine, and 3-hydroxybutyric acid—compared with insulin at comparable glycemic levels. In contrast, C4 carnitine (an earlier metabolite in valine catabolism) rose more with insulin. No corresponding between-group differences were detected in plasma metabolites. In db/db mice, luseogliflozin attenuated glomerular mesangial expansion and tubular epithelial atrophy, and reduced Col1a1 mRNA and TGF-β1 protein, compared with glargine at comparable glycemic levels. Luseogliflozin decreased the phosphorylated (inactive) form of the BCKDH E1α subunit (p-BCKDHA/BCKDHA) and lowered BCKDK protein. mRNA expression of amino acid transporters and BCAT2 expression was unchanged.Conclusions/interpretationAcross complementary human and mouse studies, SGLT2 inhibition was suggested to enhance renal BCAA catabolism compared with insulin at comparable glycemic levels. In humans, increases in urinary BCAA-derived downstream metabolites without corresponding changes in plasma support a kidney-localized metabolic effect. In mice, SGLT2 inhibitor improved renal histopathology, and reduced phosphorylation-mediated inactivation of BCKDH. These findings provide mechanistic, translational evidence that SGLT2i modulate BCAA flux independently of glucose lowering, suggesting BCAA catabolism as a therapeutic axis in diabetic kidney disease.Clinical trial registrationhttps://rctportal.mhlw.go.jp/en/detail?trial_id=UMIN000052955, identifier UMIN000052955.